Efektivitas Media Interaktif Wordwall Dengan Model Problem Based Learning Terhadap Hasil Belajar IPAS Siswa Kelas IV SD - Khana Ulin Nuha; Barokah Isdaryanti (Journal of Classroom Action Research, 2026)
This study aims to examine the effectiveness of interactive Wordwall media integrated with the Problem-Based Learning (PBL) model on the learning outcomes of fourth-grade students at Gugus Palapa Public Elementary School, Batang Regency. A quantitative approach with a non-equivalent control group quasi-experimental design was used. Participants were divided into an experimental class, which received instruction using Wordwall media with the PBL model, and a control class, which was taught using conventional learning methods. Data were collected through pretest and posttest, then analyzed using independent sample t-test and N-Gain analysis. The t-test results showed that the t-value was greater than the t-table value (6.605 > 2.015) with a significance level of 0.000 < 0.05, indicating a significant difference in learning outcomes between the two groups. In addition, the N-Gain score for the experimental class was 0.65 (moderate category), while the control class achieved a score of 0.18 (low category). The average posttest score of the experimental class (88.04) was also higher than that of the control class (71.09). These findings indicate that interactive Wordwall media combined with the PBL model is effective in improving IPAS learning outcomes in elementary schools.